O8A.3 Mining exposures and lung cancer in contemporary western australian miners. (April 2019) - Sodhi-Berry, Nita; Klerk, Nicholas de; Franklin, Peter; Reid, Alison; Fritschi, Lin; Musk, Bill; Vermeulen, Roel; Peters, Susan
Abstract : Objectives: Mining is associated with exposures to various lung carcinogens such as diesel engine exhaust (DEE) and respirable crystalline silica (RCS). We aimed to determine if lung cancer incidence was higher in Western Australian (WA) miners than the general population and if risk varied within the cohort according to exposures and work or job types. Methods: Exposure data for 1 72 398 miners living and working in WA between 1996 and 2013 was combined with administrative WA cancer and death data until June-2017. Causal Incidence Ratios (CIRs) were calculated for general population comparisons. Hazard Ratios (HRs) were derived from multivariable Cox regression models including sex, only-underground work, ore-type (gold, iron-ore, other metal, non-metal, unknown or multi-ore mines) and quantitative estimates of DEE (measured as elemental carbon) and RCS, after adjusting for ever-smoker status and entry-age. Additional analyses were done after lagging exposures by 15 years. Results: Mean DEE and RCS cumulative exposures were estimated as 0.15 mg/m3-years (std:0.37) and 0.09 mg/m3-years (std:0.18), respectively. Miners had lower lung cancer incidence than the general population (observed=382; expected=538.11; CIR:0.71, 95% CI:0.64–0.78). Within the mining cohort, higher lung cancer risks were observed for: females vs. males (HR:1.44, 95% CI:0.97–2.03); ever-smokers vs. never-smokers (HR:10.1, 95% CI:6.37–16.1); only-underground vs. only-surface miners (HR:1.72, 95% CI:1.02–2.90); only gold vs. multi-ore miners (HR:1.44, 95% CI:1.01–2.05); and only iron ore vs. multi-ore miners (HR:1.47, 95% CI:1.07–2.04). Neither DEE (HR:1.01, 95% CI:0.89–1.14) nor RCS (HR:0.89, 95% CI:0.61–1.3) was significantly associated with incidence. There was no significant difference in estimates after lagging exposures. Conclusion: Miners had lower risk of lung cancer than the general population. Workers mining exclusively in underground, iron ore or gold mines had higher lung cancer risks than their peers, as did ever-smokers and females. Low levels of DEE and RCS exposures in WA mines may explain the lack of association between these exposures and lung cancer.